Lipid-lowering in diabetes: An update - Chait, Alan; Eckel, Robert H; Vrablik, Michal; Zambon, Alberto (Atherosclerosis, 2024)
Atherosclerotic cardiovascular disease (ASCVD) is accelerated in people with diabetes. Dyslipidemia, hyperglycemia, oxidative stress, and inflammation play a role via a variety of mechanisms operative in the artery wall. In addition, some unique features predispose people with type 1 diabetes to accelerated atherosclerosis. Various organizations have created guidelines that provide advice regarding screening, risk assessment, and roadmaps for treatment to prevent ASCVD in diabetes. Management of dyslipidemia, especially with statins, has proven to be of immense benefit in the prevention of clinical CVD. However, since many patients fail to attain the low levels of low-density lipoproteins (LDL) recommended in these guidelines, supplemental therapy, such as the addition of ezetimibe, bempedoic acid or PCSK9 inhibitors, is often required to reach LDL goals. As a result, the upfront use of combination therapies, particularly a statin plus ezetimibe, is a rational initial approach. The addition to statins of drugs that specifically lower triglyceride levels has not proven beneficial, although the addition of icosapent-ethyl has been shown to be of value, likely by mechanisms independent of triglyceride lowering. Newer treatments in development, including apoC-III and ANGPTL3 inhibitors, seem promising in further reducing apoB-containing lipoproteins.
Keywords: biologické markery; Biomarkers; Dyslipidemias; výsledek terapie; anticholesteremika; lidé; Treatment Outcome; statiny; Diabetes Mellitus, Type 1; Atherosclerosis; Anticholesteremic Agents; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypolipidemic Agents; hypolipidemika; dyslipidemie; ezetimib; kombinovaná farmakoterapie; ateroskleróza; Ezetimibe; diabetes mellitus 1. typu; Drug Therapy, Combination; Humans